Multichromic Behavior of Liquid Crystalline Composite Polymeric Films - Mizuho Kondo; Satoka Yanai; Syouma Shirata; Takeshi Kakibe; Jun-ichi Nishida; Nobuhiro Kawatsuki (Crystals, 2023)
In this study, we describe the synthesis of a cholesterol-linked cyanostilobazole salt dye and the tuning of its luminescence by physical stimuli such as electricity and grinding. The dyes exhibited liquid-crystalline properties at temperatures above 170 °C. Some of the solutions were transformed into orange luminescent gels upon the addition of poor solvents. When the solvent was evaporated, the resulting solid xerogel exhibited mechanochromism, its color changed, and its luminescent color changed from orange to red. Furthermore, we investigated the construction of functional gels (mechanochromic gels) that can respond to two stimuli, damage detection by abrasive responsiveness, and electrical response using ionic liquid complexes of polymers as dispersing media. This study provides a new strategy for tuning and switching luminescence using non-chemical stimuli in a single-component system using aggregation.